Inkubator Edukasi Kewirausahaan: Optimalisasi Pandan Wangi (Pandanus amaryllifolius Roxb.) Pada Kelompok Tani di Pekon Pardasuka - Oktoba, Zulpakor; Afriyani, Afriyani; Putra Seta, Amanda; Noer Fathia, Syaharani; Ramadianti, Savira; Zahra Taslima, Tsania (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The utilization and optimization of the added value of the medicinal plant Pandanus amaryllifolius Roxb. have not yet been undertaken. The Community Service (PkM) program aims to educate members of the Jaya Lestari Farmers’ Group (POKTAN) and Women Farmers’ Group (KWT). Pandan leaves can be developed into a commercially viable product specifically, a herbal tea formulation containing stevia (Stevia rebaudiana) and rosemary (Salvia rosmarinus) to serve as an antioxidant supplement for people with diabetes. The methodology used in this Community Service Program is qualitative, involving data collection through interviews, observations, educational sessions, training, and hands-on guidance in the production of herbal tea products. The PkM program was evaluated through pre-test and post-tests; data analysis revealed a significant increase in participants’ knowledge, from 60.95% to 67.95%, as well as the positive impact of entrepreneurship education on enhancing the capacity of POKTAN partners, who have successfully developed an innovation in the production of pandan wangi leaf tea.